A Quantitative Justification of Similarity in Placebo Response Between Adults and Adolescents With Acute Exacerbation of Schizophrenia in Clinical Trials. Issue 5 (3rd July 2019) - Kalaria, Shamir N.; Zhu, Hao; Farchione, Tiffany R.; Mathis, Mitchell V.; Gopalakrishnan, Mathangi; Uppoor, Ramana; Mehta, Mehul; Younis, Islam
Abstract : Early‐onset schizophrenia, or "adolescent schizophrenia, " has a global incidence ranging up to 4% of all schizophrenia cases. Clinical data from antipsychotic programs were collected from new drug applications submitted to the US Food and Drug administration from 1993 to 2015. A placebo response–dropout model was developed to describe the time course of total positive and negative syndrome scale (PANSS) scores in adults and adolescents. The final model in both populations suggested that patients with higher baseline scores exhibited a greater absolute reduction from baseline. Higher baseline total PANSS, enrollment in US trials, and increases or small improvements in total PANSS were found to be predictors of dropout in both populations. Simulated adolescent data using the final adult placebo response model resembled the observed adolescent data. By confirming similar changes in disease symptomology during an acute exacerbation, efficient regulatory pathways for adolescents can be facilitated by using the extrapolation paradigm.